Can the recent sex-specific evolutions in elite running performances be attributed to advanced footwear technology? - Mason, J.; Starc, L.; Morin, J.-B.; McClelland, E. L.; Zech, A. (Frontiers in Sports and Active Living, 2024)
Recent improvements in elite running performances across all distances have been largely attributed to the introduction of advanced footwear technology (AFT), which features a curved and stiff plate working synergistically with a new generation of midsole foams demonstrating enhanced resilience and compliance. These recent improvements appear to be considerably more pronounced in women's events, highlighted by improvements in road racing world records by an average of 3.7% (range: 2.6%-5.2%) compared to mean progressions of 1.5% (range: 1.3%-1.9%) in the same men's events. Although there is a growing body of research investigating the mechanisms underpinning running performance enhancements derived from AFT, there remains no explanation for potential sex-based differences in their benefits. We overview the currently available evidence and highlight why the recent direction of AFT research provides a barrier to progress by focusing primarily on male athletes. We subsequently provide our perspective on why women may be benefiting from the new generation of shoes more than men, suggest potential mechanisms leading to hypotheses that need to be further investigated in upcoming studies, and finally propose that factors outside of footwear innovation may have concurrently driven the recently observed performance evolutions.